VARIOUS POSTHARVEST HANDLING PROCEDURES EXTEND LONGEVITY OF CUT Gerbera jamesonii STEMS - Tazkia Hussain; Iftikhar Ahmad; John M. Dole; Usama Jamil (Journal of Animal and Plant Sciences, 2025)
Efficient postharvest handling plays a pivotal role in preserving stem quality, which demands testing novel and cost-effective techniques for extending the postharvest longevity of cut stems. Postharvest management practices are crucial to improve cut stems longevity. Therefore, a study was conducted to evaluate and standardize postharvest handling protocols for cut gerbera stems including harvest stage, handling procedures, vase water quality, pulsing and vase preservatives, floral foam, storage methods and durations and packaging materials. Results demonstrated that stems harvested at partially opened bloom stage had the longest vase life (16.6 d) followed by closed bud stage (15.2 d). Stems kept in distilled water remained fresh for longer (8.4 d vase life) compared to tap water (5.0 d) and canal water (3.2 d). Tap water affected gerbera stems negatively with highest petal necrosis (100%) and highest reduction in flower quality (8.1) among tested water sources. Stems handled wet (in buckets containing water) had longest vase life (15.7 d) with least change in flower quality (7.2). Gerbera stems pulsed with 2% sucrose + 100 mg L-1 aluminum sulphate for 24 h exhibited longest vase life (11.4 d) followed by lemon/lime soda (7 Up) + distilled water (11.2 d). Placement of cut stems in lemon/lime soda + distilled water (33:66) until termination (vase preservatives) exhibited longest vase life (15.9 d) followed by 2% sucrose along with 150 mg L-1 citric acid and 100 mg L-1 aluminum sulphate (15.3 d, respectively) and were statistically similar. Chrysal Clear Professional flower food along with floral foam kept stems fresh and marketable for 16.9 d, while for 15.6 d without foam. Stems stored wet (in buckets containing water) or in a floral box along with 1-MCP card for 2 days exhibited longest vase life (7.8 d and 7.3 d, respectively). Flower heads packed in floral box after being wrapped in polythene sleeves and plugged with cotton tube at base exhibited the longest vase life (6.5 d) when stored for 2 days compared to control (unpacked and unstored stems). In summary, gerbera stems may be harvested at partially opened bloom stage, handled in water (wet) from harvest to marketing and preferably handled in distilled water, pulsed with 2% sucrose + 150 mg L-1 citric acid, 2% sucrose + 100 mg L-1 aluminum sulphate or lemon/lime soda + distilled water (50:50) for 24 h or kept continuously in lemon/lime soda + distilled water (33:66) until termination. Moreover, stems may be kept with floral foam and stored in buckets containing water (wet) preferably with 1-MCP card for two days and packed in floral boxes lined with polythene sleeves to keep stems fresh for longer durations.
Keywords: Floral foam; homemade preservatives; ion leakage; packaging; storage methods; termination symptoms